The problem of the specification of peerness of land plots at the exchange aiming at land consolidation - Malashevskyi, M.; Tarnopolskyi, A.; Malashevska, O.; Tarnopolskyi, Ye. (Land Management, Cadastre and Land Monitoring, 2023)
The article scrutinizes the problem of land plots exchange with the aim of the spatial land improvement. At the current stage, the problem of the removal of overlapping of agricultural lands in agricultural land masses, elaboration and improvement of land consolidation mechanisms; the implementation of compulsory complex land consolidation is under discussion; there are preconditions of the improvement of the technical substantiation of land plot alienation for public needs. In this context, the problem of the identification of the peerness of land plots is scrutinized, i.e. the recognition of land plots to be peer provided the difference of their values is less than 10%. The study aims at the improvement of approaches to the definition of the affordable difference of land plots values which can be considered peer at the exchange. The provisions of legislation have been analysed which precondition the peer land plots exchange and specify the affordable difference of values of such land plots. It has been revealed that due to the vague definition of the affordable difference of land plot value, there is the uncertainty of 1/110 (≈0,9%) to 13/220 (≈5,9%) of the value of land plot. The existence of such mistake is firstly the reason for the disputes of the equal land plots exchange in the court, secondly, it is a hurdle for the voluntary involvement of landowners to land exchange. The specification of the definition of the affordable difference of land plots values which can be considered to be equal has been suggested. The results gained can be used at the definition of land plots as the equal at exchange and sublease; at the implementation of complex land consolidation; at the alteration of legal acts on land consolidation; at the modeling of land reallotment based on the heuristic or optimizational approach. Key words: land exchange, land reallotment, peer land plots, land consolidation, land evaluation.